دراسة وتحليل تمظهرات حضور "القارئ الضمني" في مقامات الحريري مستمدا من آراء منظري نظرية التلقي - ضروني، محمد صادق; عقدا، رضا أفخمي (جامعة قاصدي مرباح - ورقلة, 2022)
إن حضور القارئ لم يكن يحظى بمكانة في الدراسات الأدبية كطرف مشارك في العلاقة التواصلية بل غايتها إلا أن ظهرت "نظرية التلقي" وحملت بيدها إن الشيء الأساس في قراءة كل عمل أدبي هو التفاعل بين بنية النص ومتلقيه؛ فناقش أصحاب نظرية التلقي مفاهيم خاصة كـ "أفق الانتظار والتفاعل بين النص والمتلقي والقارئ الضمني". فمن بين كلها وقع الاختيار في هذا البحث على القارئ الضمني، هذه البنية النصية المفترض وجودها بين سطور النص والتي يتم بموجبها تحديد الدور المنوط بالقارئ المستهدف. فحينما يكتب الكاتب؛ يكتب وفي ذهنه قارئ ما يحاول إرضاءه ويسعى إلى أن يحوز على إعجابه، ويحاول التأثير فيه. بناء على هذا فإن هذه الدراسة تدرس مدى انغماس هذا القارئ في التعامل بينه وبين قصص "مقامات الحريري" كنوع من أقدم أنواع الأدب القصصي بالاعتماد على منهج توصيفي-تحليلي؛ فيكتشف بعض سر الجمال وإمتاع القراء منها؛ حيث جاء الحريري بأسلوب ممتع والفجوات والفراغات التي يلقى الكشف عن معناها على عاتق القارئ كعدم الدخول في بعض التفاصيل الضرورية والاستفادة من الأمثال والكنايات. ومن الطبيعي أن الاهتمام بكشف معناها يدعو القارئ للتواصل مع النص ويتيح له التمتع أكثر حيث إنه يعتبر نفسه شخصية داخل النص السردي كخالق للقصة. With the emergence and expansion of literary theories in recent decades, there have been extensive changes in the field of literary criticism Undoubtedly, one of these theories that attracted the attention of many critics and writers was the "theory of reception" Because this theory, by reviewing the relations between the author, the work and the reader, changed its main axis in the study of literary texts from "author / text" to "text / reader" In fact, placed the reader in the center of the author's attention as a very important element so that he could write his work in accordance with the needs of the audience. The pioneers and the followers of this theory in the analysis of literary texts tried to study various concepts such as "waiting horizon, changing horizon, Implicit Reader, etc". This article tries to examine the author's attention to this important element in literary creations that is manifested in literary texts by examining the Implicit Reader in Hariri maqamat as an ancient type of fiction and Finally, discover the secret of beauty and readers' enjoyment of this ancient kind of story. In this regard, it was found that the author by creating gaps in the text of the maqamat, such as not entering some necessary details and using proverbs and allusions, has been able to accompany the reader to discover these spaces and gaps in the text. To the extent that in some maqameh, the reader is immersed in the text in order to discover them, so that he considers himself one of the characters in the text of the story, and this in turn doubles his satisfaction with reading the maqamat.
Keywords: النقد الأدبي -- نظرية التلقي -- فن المقامات -- القارئ الضمني -- البناء السردي